2012
DOI: 10.1177/0886260512468250
|View full text |Cite
|
Sign up to set email alerts
|

The Average Predictive Validity of Intimate Partner Violence Risk Assessment Instruments

Abstract: The field of intimate partner violence (IPV) risk assessment (predicting recidivism, lethality) is fast growing, and the majority of research examining the predictive validity of IPV risk assessment instruments has been conducted in the past decade. This study examines the average predictive validity weighted by sample size of five stand alone IPV risk assessment instruments that have been validated in multiple research studies using the Receiver Operating Characteristic Area Under the Curve (AUC). The Ontario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
229
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(242 citation statements)
references
References 60 publications
(111 reference statements)
6
229
2
5
Order By: Relevance
“…Such tools are utilized to identify defendants who may be at greater risk of recidivism or failure to appear in court as well as maximize efficiency with limited resources (Andrews and Bonta, 1998). The predictive validity of these tools continues to be refined and has increased over time (Messing et al, 2015;Messing and Thaller, 2013). Consistent shortcomings of these risk instruments include failure to accurately collect the required information and the perception of criminal justice personnel that such tools undermine their professional skills and judgment (Andrews and Bonta, 1998;Aubrey and Hough, 1997).…”
Section: Role Of Police As Integrators Of Risk Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such tools are utilized to identify defendants who may be at greater risk of recidivism or failure to appear in court as well as maximize efficiency with limited resources (Andrews and Bonta, 1998). The predictive validity of these tools continues to be refined and has increased over time (Messing et al, 2015;Messing and Thaller, 2013). Consistent shortcomings of these risk instruments include failure to accurately collect the required information and the perception of criminal justice personnel that such tools undermine their professional skills and judgment (Andrews and Bonta, 1998;Aubrey and Hough, 1997).…”
Section: Role Of Police As Integrators Of Risk Assessment Toolsmentioning
confidence: 99%
“…Research has demonstrated that a large and expanding proportion of U.S. police agencies employ some form of IPV/DV risk assessment instrument (Messing et al, 2015;Police Executive Research Forum, 2015) while police in the U.K. have utilized the Domestic Abuse, Stalking, and Honor Based Violence risk assessment tool since 2009 (Robinson et al, 2016). Despite wide recognition that police should, and have been, adopting risk-led approaches to IPV/DV, the utility of this approach continues to be hindered by practical shortcomings (Bland and Ariel 2015;Hoyle, 2007).…”
Section: Role Of Police As Integrators Of Risk Assessment Toolsmentioning
confidence: 99%
“…The majority of research studies on risk assessment for domestic violence have focused on the accuracy with which specific tools can predict future assaults. A meta-analyses by Messing and Thaller (2013) concluded broadly that existing risk assessment tools had moderate levels of predictive validity and that it was difficult to advocate one over another due to methodological variability in the validation studies and the different stated purposes of the tools themselves.…”
mentioning
confidence: 99%
“…Knowledge on the predictive validity of IPV risk assessments has been examined and summarized in a number of recent review studies, e.g. Helmus andBourgon (2011), Messing andThaller (2013) and Nicholls, Pritchard, Reeves and Hilterman (2013), all of which are described below. However, I have not been able to find any previous reviews examining the predictive validity of IPV assessments conducted by practitioners in different settings specifically, and this will be the focus of the present study.…”
Section: Funding Sourcesmentioning
confidence: 99%
“…For instance, Nicholls et al (2013) presented AUC values ranging between .48 and .92, and Helmus andBourgon (2011) between .59 and.87. Messing andThaller (2013) presented the average AUCs of different tools, which had a smaller range (.54-.67). As was mentioned previously, predictive validity is influenced by many factors, which makes it difficult to compare results from different studies.…”
mentioning
confidence: 97%